Smart home: Keeping privacy based on Air‐Padding - Quanlong Zhu; Chao Yang; Yu Zheng; Jianfeng Ma; Hui Li; Junwei Zhang; Jiajie Shao (IET Information Security)
Abstract With the rapid development of the IoT, smart home plays an increasingly important role in daily life. At the same time, privacy issues have gradually aroused the concern of researchers. Past research proves that there are privacy risks when people use smart home devices and some protection methods are proposed to protect people's privacy. However, attackers can still infer people's behaviour and activities through analysing the wireless traffic of smart home devices. Herein, an attack method under complicated WiFi scenarios is demonstrated, including different locations, different buildings and different networks. In addition, a new protection method, Air‐Padding, is developed, which can change the traffic patterns of smart home devices through injecting constructed packets into the link between devices and routers. The results prove that Air‐Padding can prevent people's behaviour and activities from being analysed and inferred.